Storytelling: recontextualizing language in literacy for student learning - Luciana Backes; Vera Lúcia Felicetti; Fabiane Aparecida Parcianello de Almeida (Signo)
The article discusses the recontextualization of language, through storytelling, in literacy to overcome student learning difficulties, based on teacher training. The aim is to identify relevant aspects in storytelling that enhance the learning of students in the process of literacy. Thus, we established a dialogue between different perspectives on literacy to recontextualize written language. The case study included the application of pre- and post-tests to 3rd grade students in the Canoas/RS municipal school system, training for the teachers of these students and pedagogical practices. Based on the data analyzed quantitatively, we found that storytelling makes it possible to explore and construct different situations, contextualizing written language in the expression of meanings and the construction of hypotheses, as well as problematizing everyday life through the stories experienced.